FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA KELAPA SAWIT DI DESA LEMBAH HIJAU 1 KABUPATEN KETAPANG - Rabiatul Adawiyah; Heri Wijayanto; Sri Hartono (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to determine the factors that can influence interest in entrepreneurship in oil palm entrepreneurship in the village of Green Valley 1, Ketapang district. The population used in this study were all village people who work as oil palm farmers with a sample of 75 respondents. In this study, the sampling method used is non-probability sampling, namely accidental sampling. Data collection techniques were carried out by distributing questionnaires to village communities who work as oil palm farmers. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that 1) Family business has a positive and significant effect on the interest in entrepreneurship for oil palm smallholders in Lembah Hijau 1 Village, Ketapang Regency with a significance of 0.002. 2) Work experience has no effect on the interest in entrepreneurship for oil palm smallholders in Lembah Hijau 1 Village, Ketapang Regency with a significance of 0.354. 3) The social environment has a positive and significant effect on the interest in entrepreneurship for oil palm smallholders in Lembah Hijau 1 Village, Ketapang Regency with a significance of 0.047. 4) the independent variables jointly affect the interest in entrepreneurship by 41.5% while the remaining 58.5% is influenced by other variables